Effective thermal conductivity of beans via a steady-state method - Thomeo, J. C.; Costa, M V A; Filho, J F L (Marcel Dekker Inc, 2004)
Steady-state concentric cylinder equipment was used to determine the effective thermal conductivity of beans (Phaseolus vulgaris). The measuring cell had no heated end guards and its length to diameter ratio was 10.5. Glass beads were employed to assess the accuracy and repeatability of the experimental system under heat transfer conditions. The results agree well with those reported in the literature so that the system can be considered reliable. Corn was used to verify the system's accuracy under heat and mass transfer conditions. Again the results were satisfactory. Moisture migration was observed and measured during the tests with beans, but this behavior does not compromise thermal conductivity values if both thermal and mass transfer steady-states are correctly interpreted. The effective thermal conductivity increases linearly with increasing grain moisture content. Statistical regression leads to good estimates of the fitted parameters.
Keywords: heat transfer; porous media; packed bed; physical properties of foods; thermal conductivity; beans